Pengelompokan Klon-Klon Ubi Jalar Berdasarkan Analisis Gerombol, Komponen Utama dan Biplot dari Karakter Morfologi - Hetharie, Helen; Raharjo, Simon Hadi Teguh; Jambormias, dan Edizon (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2018)
Sweet potato is a food crop with high genetic and phenotypic diversities. The objective of this study was to cluster sweet potato clones based on their morphological characters. This research used descriptive method using 25 morphological characters on 28 sweet potato clones and clustered using dice coefficient, principal component analysis and biplot analysis. The results showed that the clones were grouped into two clusters and 14 sub-clusters. Three sub-clusters had high similarity coefficients, i.e., 0.68-0.96, one clone was eliminated, and 11 sub-clusters had a low similarity, i.e., 0.41-0.52. The principal component analysis showed 14 of 25 morphological characters determined the diversity in 27 sweet potato clones with cumulative variance of 70.79%. Biplot analysis showed that 12 characters contributed to cumulative variance of 61.3%. Twelve morphological characters had weak contribution on the characteristics of the clones in quadrant I; meanwhile, characteristics of clones in quadrant II were orange, yellow and white tuber flesh, in quadrant III was dark purple tuber flesh, and in quadrant IV were purple tuber flesh and cortex. Result of the grouping analysis identified clones that were closely related and those distantly related for improvement purposes.Keywords: Ipomoea batatas, cumulative variance, Maluku province, morphology, relationship